Gundala Small Medium Enterprise Production Planning and Inventory Control System - AVICENNA, FADHILAH ATHHAR FAUZI; Mohd Safar, Noor Zuraidin (Applied Information Technology And Computer Science, 2024)
Manufacturing Resource Planning (MRP) and inventory control are the cores for Small-Medium Enterprise (Sme) to works efficiently in keeping records for inventory and plannings for production efficiently. The system involved in every aspect and procedure regarding inventory control which coexist alongside manufacturing sector to achieve the most effective approach. A web-based Production Planning and Inventory Control (PPIC) system was developed to maximize the availability of the system for usage which provides more flexibility and less limitation for task executions. The prototype method is used to deliver this system for its compatible method. Identifying the issue statement, objectives, system requirements, building the system interface, and constructing the database are all part of the system construction procedures. The system developed in PHP and MySQL under Visual Studio Code. The system is intended to improve the entire operation effectiveness of PPIC and expected to be maintained and enhanced in the long term.